Reduced Child-Oriented Face Mirroring Brain Responses in Mothers With Opioid Use Disorder: An Exploratory Study - Swain, James E.; Ho, S. Shaun (Frontiers in Psychology, 2022)
The prevalence of opioid use disorder (OUD) among pregnant women has multiplied in the U.S in the last decade. Buprenorphine treatment (BT) is standard for peripartum women with OUD to reduce risks of repeated cycles of craving and withdrawal. However, mothers with OUD may be at additional risk for altered activity in the opioid sensitive maternal behavior neurocircuit (MBN) that regulates maternal behavior and bonding. In the regulation rodent maternal behaviors such as licking and grooming, a series of opioid sensitive brain regions are functionally connected, including the ventral pallidum (VP). In humans, these brain regions, interact with the supplementary area (SMA) to regulate maternal behaviors and are functionally dysregulated by opioids. It is unclear how these brain regions respond to their child's emotions for mothers receiving BT. We conducted a functional magnetic resonance imaging (fMRI) pilot study in 22 mothers within the first postpartum year, including 6 mothers receiving BT and 16 non-OUD mothers as a comparison group (CG). We devised a Child Face Mirroring Task (CFMT) for functional magnetic resonance imaging to assess maternal responses to own child and an unknown child's pictures of facial expressions in three conditions: 1) empathic mirroring (Join), 2) non-mirroring observation (Observe), and 3) volitional child-oriented responses (React). In each condition, each child's neutral, ambiguous, distressed, and joyful expressions were repeatedly displayed in a random order. The response of supplemental motor area (SMA) during empathic mirroring (Join) vs. non-mirroring (Observe) of Own Child was reduced among BT/OUD vs. CG. Within MBN, the left VP, critical for parental sensitivity, had a similar deficit. This study outlines potential mechanisms for investigating the risks of deficits in the neural responses to actual maternal sensitivity and parenting behavior in mothers with OUD, and potential targets for interventions that reduce stress and augment maternal behavior, and child outcome.